Iklan Video Produk Menggunakan Aplikasi Adobe Premiere Di Instagram Pada UMKM Rosya - Daffa Arya Kumara; Dwi Sudjanarti (CV. ITTC INDONESIA, 2024)
Rosya Singosari Malang is engaged in the herbal sector. UMKM Rosya advertises its products via Whatsapp, Instagram, and also introduces its products through events in the city of Malang. However, the content on social media owned by UMKM Rosya, is still less interesting. This research aims to develop product video content on Instagram so that the quality of advertising increases. The research method used was action research involving 15 respondents consisting of 2 computer experts, 1 owner, and 12 consumers or potential consumers. Meanwhile, the data collection methods used were observation, interviews, questionnaires, and documentation. The results of the questionnaire were analyzed using the EPIC Model to measure the level of effectiveness of product videos. The research results showed that the level of effectiveness of product videos was in the very effective category with an EPIC model score of 4.2. These results indicated that the product video developed was suitable for use. From the results of this research it can be concluded that the product videos developed are very effective to be used as advertisements on Rosya UMKM Instagram.